Process virtualization theory (PVT) and institutional theory (INT) to explain SAAS adoption - Tomás, Sara Cristina dos Santos (2015)
Software as a service (SaaS) is a service model in which the applications are accessible from various client devices through internet. Several studies report possible factors driving the adoption of SaaS but none have considered the perception of the SaaS features and the pressures existing in the organization’s environment. We propose an integrated research model that combines the process virtualization theory (PVT) and the institutional theory (INT). PVT seeks to explain whether SaaS processes are suitable for migration into virtual environments via an information technology-based mechanism. INT seeks to explain the effects of the institutionalized environment on the structure and actions of the organization. The research makes three contributions. First, it addresses a gap in the SaaS adoption literature by studying the internal perception of the technical features of SaaS and external coercive, normative, and mimetic pressures faced by an organization. Second, it empirically tests many of the propositions of PVT and INT in the SaaS context, thereby helping to determine how the theory operates in practice. Third, the integration of PVT and INT contributes to the information system (IS) discipline, deepening the applicability and strengths of these theories.